Tumor growth manifested in two-fifths of low-risk papillary thyroid microcarcinoma patients during active surveillance: data from a tertiary center in China - Le, Kehao; Jin, Lei; Zhong, Fangfang; Huang, Xiaojuan; Zhou, Liang; Zhou, Jiamin; Xie, Lei (Frontiers in Endocrinology, 2024)
PURPOSE: To assess tumor growth using tumor doubling rate (TDR) during active surveillance (AS) in China.METHODS：Between January 2016 and June 2020, a total of 219 patients with low-risk papillary thyroid microcarcinoma (PTMC) (aged 23-75 years) were consecutively enrolled in the AS program.RESULTS: Four sections of TDR, >0.5, 0.1~0.5, -0.1~0.1 and <-0.1, corresponded with four categories of tumor volume kinetics: rapid growth, slow growth, stable, and decreased size. We found that 10.5% of PTMCs exhibited rapid growth, 33.33% exhibited slow growth, 26.48% were stable, and 29.68% decreased in size. Tumor growth was associated with two factors: age and volume of PTMC at diagnosis. 85.72% of elderly patients (≥ 61 years old) had tumors that remained stable or even shrank and rapidly growing tumors were not found in them. When the volume was small (≤14.13 mm 3 ), the proportion of rapid growth was high (41.67%), whereas when the volume was large (> 179.5 mm 3 ), the proportion of non-growth was 68.75%.CONCLUSION: TDR may be a better metric for evaluating tumor growth in observational PTMCs.A certain proportion of PTMCs grow during the period of AS and tumor growth was associated with age and volume of PTMC at initial diagnosis. Therefore, how to block tumor growth during the AS period, especially for young patients and patients with early-stage PTMC (size ≤ 5 mm), will be a new challenge.